Defects in the Proteome and Metabolome in Human Hypertrophic Cardiomyopathy. (11th May 2022) - Previs, Michael J.; O'Leary, Thomas S.; Morley, Michael P.; Palmer, Bradley M.; LeWinter, Martin; Yob, Jaime M.; Pagani, Francis D.; Petucci, Christopher; Kim, Min-Soo; Margulies, Kenneth B.; Arany, Zoltan; Kelly, Daniel P.; et al.
Abstract : Background: Defects in energetics are thought to be central to the pathophysiology of hypertrophic cardiomyopathy (HCM); yet, the determinants of ATP availability are not known. The purpose of this study is to ascertain the nature and extent of metabolic reprogramming in human HCM, and its potential impact on contractile function. Methods: We conducted proteomic and targeted, quantitative metabolomic analyses on heart tissue from patients with HCM and from nonfailing control human hearts. Results: In the proteomic analysis, the greatest differences observed in HCM samples compared with controls were increased abundances of extracellular matrix and intermediate filament proteins and decreased abundances of muscle creatine kinase and mitochondrial proteins involved in fatty acid oxidation. These differences in protein abundance were coupled with marked reductions in acyl carnitines, byproducts of fatty acid oxidation, in HCM samples. Conversely, the ketone body 3-hydroxybutyrate, branched chain amino acids, and their breakdown products, were all significantly increased in HCM hearts. ATP content, phosphocreatine, nicotinamide adenine dinucleotide and its phosphate derivatives, NADP and NADPH, and acetyl CoA were also severely reduced in HCM compared with control hearts. Functional assays performed on human skinned myocardial fibers demonstrated that the magnitude of observed reduction in ATP content in the HCM samples would be expected to decrease the rate of cross-bridge detachment. Moreover, left atrial size, an indicator of diastolic compliance, was inversely correlated with ATP content in hearts from patients with HCM. Conclusions: HCM hearts display profound deficits in nucleotide availability with markedly reduced capacity for fatty acid oxidation and increases in ketone bodies and branched chain amino acids. These results have important therapeutic implications for the future design of metabolic modulators to treat HCM.